Large Bleeding Tonsillar Mass in a Child - Rare Presentation of Non-Hodgkin Lymphoma - Bhat Y, Ramesh; Patil, Anand Kumar (Journal of Nepal Paediatric Society, 2020)
Tonsillar malignancy is the underlying etiology of only a very small percentage of paediatric unilateral tonsillar enlargements. Further, because of rarity of tonsillar malignancy in children, the diagnosis may be delayed. Authors describe a large bleeding tonsillar mass in a child who remained undiagnosed for two months but finally diagnosed with non-Hodgkin lymphoma at the institution.